The enlightenment of bees [large type] - Linden, Rachel (Center Point Large Print, 2019)
Mia West has her entire life planned out: a cottage in Seattle, baking at The Butter Emporium, and her boyfriend Ethan by her side. Alone and adrift when her plans crumble, she decides to find new meaning in her life by helping those in need. Guided by recurring dreams about honeybees, Mia joins her housemate Rosie on an around-the-world humanitarian trip funded by a reclusive billionaire, Lars Lindstrom. As an eclectic group embarks on the trip from the slums of Mumbai to a Hungarian border camp during the refugee crisis, Mia's idealistic vision is challenged and circumstances force her to choose between the life she thought she wanted and the life she has built. -- adapted from back cover